2022
DOI: 10.3390/v14071538
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 and Interferon-Gamma Are Released by Natural Killer Cells upon Activation with Interferon-Alpha and Orchestrate the Suppression of Hepatitis C Virus Infection

Abstract: Natural killer (NK) cells mount an immune response against hepatitis C virus (HCV) infection and can be activated by several cytokines, including interleukin-2 (IL-2), IL-15, and interferon-alpha (IFN-α). By exploiting the Huh7.5 hepatoma cell line infected with the HCV JFH1 genome, we provide novel insights into the antiviral effector functions of human primary NK cells after cytokine stimulation. NK cells activated with IFN-α (IFNα-NKs) had enhanced contact-dependent and -independent responses as compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 90 publications
0
4
0
1
Order By: Relevance
“…However, since IFN-α also induced IFN-γ, the observation could be partly secondary to IFN-γ. In line with this, IL-2/IL-15 treatment of NK cells did not induce the secretion of IFN-γ and galectin-9 [ 118 ].…”
Section: Indirect Relationship Between Galectins and Cytokinesmentioning
confidence: 73%
See 1 more Smart Citation
“…However, since IFN-α also induced IFN-γ, the observation could be partly secondary to IFN-γ. In line with this, IL-2/IL-15 treatment of NK cells did not induce the secretion of IFN-γ and galectin-9 [ 118 ].…”
Section: Indirect Relationship Between Galectins and Cytokinesmentioning
confidence: 73%
“…In our study, the anti-inflammatory IL-10 also induced galectin-9 expression, albeit to a lesser extent than IFN-γ, while other cytokines (IL-1, TNF-α, VEGF) had no or a slightly inhibitory effect [ 13 ]. Recently, Carreca and coworkers reported that secretion of galectin-9 by NK cells was increased upon treatment with IFN-α [ 118 ]. However, since IFN-α also induced IFN-γ, the observation could be partly secondary to IFN-γ.…”
Section: Indirect Relationship Between Galectins and Cytokinesmentioning
confidence: 99%
“…The gut microbiota can influence the host’s immune response to viral infections by regulating the production of antiviral cytokines and modulating the activity of immune cells. For example, gut bacteria can produce SCFAs, which have been shown to enhance the antiviral immune response by increasing the production of IFN-γ and natural killer (NK) cells ( Carreca et al, 2022 ; Govers et al, 2022 ). Moreover, the gut microbiota can influence the development and function of Tregs, which play a crucial role in maintaining immune homeostasis and preventing excessive inflammation ( Smigiel et al, 2014 ).…”
Section: The Role Of Gut Microbiota In Sars-cov-2 Infectionmentioning
confidence: 99%
“…T-Li, natural killer (NK), and NK-T cellular concentrations and phenotypes were retrospectively analyzed in a consecutive series of liver perfusates (LPs) after hepatectomy of whole livers on the bench recovered from deceased brain donors (DBDs). Leucocytes were isolated from the perfusion fluid of liver explants, as previously described [13][14][15]. Briefly, during the organ procurement, the aorta was clamped, and the abdominal cavity was flushed with up to 5 L of preservation solution to exsanguinate the deceased donor.…”
Section: Donor Cohort and Liver Perfusate Fraction Analysismentioning
confidence: 99%